Effect of Antimony (Sb) Substitution on Ba-Site of Porous Structured YBA2Cu3OÎ´ Superconductor - Farha Ramli, Fariesha; Hashim, Azhan (International Journal of Engineering and Technology, 2018)
The effect of antimony (Sb) substitution on Ba-site of porous structure YBa2Cu3OÎ´ (YBCO) superconductor was investigated. Polycrystalline sucrose was used to create the open pores in the structure. A series of sample with a nominal composition of YBa2-xSbxCu3OÎ´ where x = 0.05, 0.10, 0.15, 0.20, 0.30, 0.40 and 0.50 were synthesized and characterized using X-ray diffraction (XRD) method, resistivity measurement technique and Scanning Electron Microscopic (SEM) equipment. For porous Sb-doped sample with x â‰¤ 0.30, the samples showed metallic behavior above onset critical temperature (TC onset) while semiconducting behavior was shown for x Â³ 0.40. The optimum Sb concentration was achieved at x = 0.15, where TC zero is 85 K and critical current (JC) value measured at 70 K is 2.75 A/cm2. TC onset and TC zero of the sample were suppressed towards higher Sb concentration. High level of Sb concentration resulted in the non-superconducting sample and Sb was not incorporated properly into YBCO system. Generally, the crystallographic structure with 123 phase remains as orthorhombic. But, for Sb doping at x = 0.30, the sample exhibits tetragonal structure before the presence of 211 phase with the higher Sb concentration. SEM micrograph for porous sample showed the less dense packing with irregular grain shape compared to the standard sample where the small rounded particles grains that can be clearly seen. It can be summarized that the superconducting properties were attributed mainly by the dopants compared to the porous characteristic.Â